Diaphragm and lithium ion battery
By using polymer microspheres in lithium-ion batteries, the problems of thermal runaway and lithium dendrites of lithium-ion batteries are solved, the safety performance and cycle stability of the battery are improved, and efficient thermal management and safety of lithium-ion batteries are achieved. Performance improvement.
Patent Information
- Application Number
- CN202411602209.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-27
AI Technical Summary
Lithium-ion batteries face thermal runaway and lithium dendrites in practical applications, which affect safety performance and cycle life.
A separator including polymer microspheres is adopted, which consists of repeating units A, B and C. The structure of repeating unit B is *-CH2-CH(OCOCH3)-, which inhibits lithium during the cycle of lithium-ion battery. uneven deposition and nucleation/growth of the product and melt at high temperatures to prevent lithium ions from transporting and prevent thermal runaway.
Effectively inhibit the generation and transmission of lithium dendrites, improve the safety performance and cycle stability of lithium-ion batteries, avoid thermal runaway accidents, and extend the service life of the battery.
Smart Images

Figure CN119208907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a diaphragm and a lithium ion battery comprising the diaphragm. Background Art
[0002] With the rapid development of electric vehicles, energy storage systems and portable electronic devices, the performance and safety of lithium-ion batteries, as their core power source, have received increasing attention from both inside and outside the industry. However, lithium-ion batteries face two key challenges in practical applications: thermal runaway of battery separators and the generation of lithium dendrites. Thermal runaway of lithium-ion batteries refers to the exothermic chain reaction of battery cells under specific conditions (such as overcharging, overdischarging, short circuit or high temperature overheating), which causes the battery temperature to rise sharply, which may cause fire or even explosion. Lithium dendrites are tree-like crystals formed by the uneven deposition of lithium ions on the surface of the negative electrode. Lithium dendrites not only cause an irreversible decrease in the number of lithium ions inside the battery, but also gradually penetrate the separator as they grow, causing direct contact between the positive and negative electrodes of the battery, causing a short circuit, and seriously affecting the safety performance and cycle life of the battery. Summary of the invention
[0003] Research has found that the main cause of thermal runaway is the abnormal increase in temperature inside the battery, which triggers a series of complex chain reactions. Among them, the diaphragm, as a key component inside the battery, is prone to shrinkage, melting, or even collapse at high temperatures, resulting in direct contact between the positive and negative electrodes of the battery, forming an internal short circuit, thereby accelerating the thermal runaway process. The main cause of lithium dendrites is that during the long-term charge and discharge cycle of lithium-ion batteries, especially under high-rate discharge or overcharging conditions, the deposition of lithium ions in the negative electrode and electrolyte becomes uneven, thereby forming lithium dendrites.
[0004] In order to overcome the significant impact of thermal runaway and lithium dendrites on the performance and safety of lithium-ion batteries, the present invention provides a diaphragm and a lithium-ion battery comprising the diaphragm. The diaphragm of the present invention can improve the uneven deposition of lithium ions during the cycle of the lithium-ion battery, curb the nucleation / growth of lithium, and thus inhibit lithium dendrites. When the lithium-ion battery has thermal runaway, the diaphragm of the present invention has a low closed-cell temperature and can melt when the temperature rises, cutting off the circuit inside the lithium-ion battery, thereby avoiding short circuits and thermal runaway accidents in the battery, thereby improving the thermal stability and anti-lithium dendrite performance of the lithium-ion battery.
[0005] In order to achieve the above object, the first aspect of the present invention provides a diaphragm, wherein the diaphragm comprises polymer microspheres, the polymer microspheres comprise repeating units A, repeating units B and repeating units C, the structural formula of repeating unit B is *-CH2-CH(OCOCH3)-*, the repeating units A and the repeating units C each independently comprise a substituted or unsubstituted C2-6 alkyl, One or more of the substituted substituents are selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3, * represents a connection end; the end group of the polymer microsphere is the repeating unit A and / or the repeating unit C, and the weight proportion of the repeating unit B in the polymer microsphere is 3%-10%.
[0006] A second aspect of the present invention provides a lithium ion battery, which includes the separator described in the first aspect of the present invention.
[0007] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0008] The diaphragm of the present invention has dual functions. On the one hand, the diaphragm of the present invention can inhibit the generation and continuous growth of lithium dendrites during the cycle of the lithium-ion battery, and prevent the lithium dendrites from penetrating the diaphragm to cause a direct short circuit between the positive and negative electrodes of the lithium-ion battery, thereby improving the safety performance and cycle stability of the lithium-ion battery; on the other hand, when the temperature of the lithium-ion battery soars to above 150°C, the diaphragm loses its strength due to shrinkage, resulting in unexpected conduction between the positive and negative electrodes, causing safety hazards. The diaphragm of the present invention has the advantage of low-temperature closed-cell. When the lithium-ion battery has not yet reached the thermal runaway temperature, the polymer microspheres in the diaphragm melt, thereby quickly closing the pores of the diaphragm, realizing autonomous thermal shutdown, preventing the transmission of lithium ions, and avoiding thermal runaway of the lithium-ion battery, thereby improving the thermal stability and safety of the lithium-ion battery.
[0009] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0010] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 The figure shows one of the structural schematic diagrams of the diaphragm in one embodiment of the present invention.
[0012] Figure 2 It is a schematic diagram of the polymer microsphere layer after melting in one embodiment of the present invention.
[0013] Figure 3 The figure shows the second schematic diagram of the structure of the diaphragm in one embodiment of the present invention.
[0014] Figure 4 The third schematic diagram of the structure of the diaphragm in one embodiment of the present invention is shown.
[0015] Figure 5 The fourth schematic diagram of the structure of the diaphragm in one embodiment of the present invention is shown.
[0016] Figure 6 The fifth structural diagram of the diaphragm in one embodiment of the present invention is shown.
[0017] Figure 7 FIG. 1 is a schematic diagram of a composite layer after melting in one embodiment of the present invention. DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.
[0019] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.
[0020] The first aspect of the present invention provides a membrane, wherein the membrane comprises polymer microspheres, the polymer microspheres comprise repeating units A, repeating units B and repeating units C, the repeating unit B has a structural formula of *-CH2-CH(OCOCH3)-*, the repeating unit A and the repeating unit C each independently comprise a substituted or unsubstituted C2-6 alkyl, One or more of the substituted substituents are selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3, * represents a connection end; the end group of the polymer microsphere is the repeating unit A and / or the repeating unit C, and the weight proportion of the repeating unit B in the polymer microsphere is 3%-10%.
[0021] The polymer microspheres may be copolymers. The weight proportion of the repeating unit B in the polymer microspheres may be 3%-10% (e.g., 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%). Studies have shown that controlling the weight proportion of the repeating unit B (group -CH2-CH(OCOCH3)-) in the polymer microspheres can change the sequence distribution properties of the polymer microspheres, thereby achieving the effect of regulating the melting point of the polymer microspheres. Controlling the weight proportion of the group -CH2-CH(OCOCH3)- in the polymer microspheres within the above range can make the melting point of the polymer microspheres lower than the temperature at which thermal runaway of the lithium-ion battery occurs. When the weight proportion of the repeating unit B in the polymer microspheres is less than 3%, the melting point of the polymer microspheres is higher than 140°C. At this time, the substrate layer in the battery separator is prone to rupture when the temperature is above 140°C, resulting in separator failure. However, the thermal response of the polymer microspheres cannot provide a thermal shutdown function for the separator within the effective working temperature of the separator (140°C). When the weight proportion of the repeating unit B in the polymer microspheres is higher than 10%, the melting point of the polymer microspheres will be lower (lower than 80°C), and irreversible melting will occur during the formation stage of battery cell preparation, causing problems in the battery cell manufacturing process.
[0022] The polymer microspheres include repeating units A, repeating units B and repeating units C, wherein the structural formula of repeating unit B is *-CH2-CH(OCOCH3)-*, and the repeating units A and C each independently include substituted or unsubstituted C2-6 alkyl, One or more of .
[0023] The substituted substituent may be selected from a cyclopropane group or a polar group, and the polar group may be selected from, for example, halogen, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3. From the specific selection of repeating unit A, repeating unit B and repeating unit C, it can be seen that the polymer microspheres include a group -CH2-CH(OCOCH3)-. It has been found through research that this group has a great influence on the melting point of the polymer microspheres. By controlling the weight proportion of the group -CH2-CH(OCOCH3)- in the polymer microspheres, the melting point of the polymer microspheres can be made lower than the temperature at which thermal runaway occurs in the lithium-ion battery, so that the polymer microspheres can be melted before thermal runaway occurs in the lithium-ion battery, and the low-temperature closure of the diaphragm pores is achieved, and thermal runaway of the lithium-ion battery is avoided, thereby improving the safety performance of the lithium-ion battery. In addition, there are hydrogen bonds and / or conjugation between the repeating units A, B and C. These interaction forces help to enhance the crystallinity of the copolymer, thereby facilitating the improvement of the melting point of the polymer microspheres. At the same time, Formula I also includes an ester group (-COO-). The oxygen in the ester group can provide a lone electron pair, which can be complexed with lithium ions to provide an anchor point for the transmission of lithium ions. At the same time, the group has a strong polarity and is effective for Li + With electrostatic attraction, accelerate Li + transmission, guiding Li + Uniform deposition can alleviate the nucleation / growth of "dead" Li, realize a highly reversible lithium plating / stripping process, avoid the occurrence of lithium dendrites, and improve the cycle stability and safety performance of the battery. In addition, the wettability of the electrolyte and the liquid retention rate of the diaphragm have an impact on the rate performance and cycle life of the lithium ion battery. The polymer microspheres of the present invention include ester groups, which are hydrophilic and have good affinity for the electrolyte, and can effectively improve the wettability of the electrolyte to the diaphragm. Formula I includes a halogen-substituted C1-6 alkyl group, and the presence of this group can inhibit the swelling of the polymer microspheres in the electrolyte, so that the polymer microspheres can improve the wettability of the electrolyte to the diaphragm while also inhibiting its swelling in the electrolyte, thereby ensuring that the liquid retention rate of the diaphragm including the polymer microspheres is not reduced, so that the lithium ion battery still maintains a high rate performance and a long cycle life.
[0024] The end groups of the polymer microspheres are the repeating unit A and / or the repeating unit C. In the present invention, the end groups of the polymer microspheres refer to the groups located at the ends (i.e., the head end and the tail end) on both sides in the structural formula of the polymer microspheres. The end groups of the polymer microspheres can be the repeating unit A, can be the repeating unit C, or can be the repeating unit A and the repeating unit C.
[0025] In the present invention, by adding polymer microspheres to the separator and controlling the weight proportion of the group -CH2-CH(OCOCH3)- in the polymer microspheres, compared with the prior art, the lithium-ion battery can have higher cycle stability and higher safety performance without affecting the rate performance and cycle life of the lithium-ion battery. In order to further improve the effect, one or more of the technical features can be further optimized.
[0026] The repeating unit A and the repeating unit C may be the same or different, and each independently comprises a substituted or unsubstituted C2-6 alkyl, One or more of .
[0027] In the present invention, substituted or unsubstituted C2-6 alkyl means that the alkyl may be substituted by a substituent or may not be substituted by any substituent. When the alkane group is substituted by a halogen, one H in the alkane group may be substituted by a halogen, multiple H may be substituted by a halogen, or all H may be substituted by a halogen.
[0028] When the repeating unit A and the repeating unit C are selected from substituted or unsubstituted C2-6 alkyl groups and the repeating unit A and the repeating unit C are located at non-terminal positions (neither the head end nor the tail end), the repeating unit A and the repeating unit C both have two connecting ends. At this time, the repeating unit A and the repeating unit C can both satisfy the structure of the polymer microspheres. For example, when the repeating unit A is an ethyl group and the repeating unit A is located at a non-terminal position, the structure of the ethyl group is *-CH2-CH2-*.
[0029] In one example, the repeating unit A and the repeating unit C each independently include a substituted or unsubstituted C2-4 alkyl, One or more of .
[0030] In one example, the repeating unit A and the repeating unit C are each independently selected from ethyl, monochloroethyl, propyl, oxirane, difluoroethyl, One or more of .
[0031] The substituted substituents may be selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3.
[0032] The substituted substituents may be selected from chlorine, fluorine, cyclopropane, propoxy, butoxy, -COOH, -O-, -COOCH3.
[0033] The halogen may be one or more of fluorine, chlorine, bromine and iodine.
[0034] In one example, the halogen is fluorine.
[0035] In one example, at least one of the repeating unit A and the repeating unit C includes a substituted or unsubstituted C2-6 alkyl group, for example, the repeating unit A includes a substituted or unsubstituted C2-6 alkyl group, or the repeating unit C includes a substituted or unsubstituted C2-6 alkyl group, or the repeating unit A and the repeating unit C both include a substituted or unsubstituted C2-6 alkyl group.
[0036] In one embodiment, the monomer forming the repeating unit B is vinyl acetate.
[0037] In one example, the monomers forming the repeating unit A include substituted or unsubstituted C2-4 olefins, One or more of the substituted groups are selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3.
[0038] In one example, the monomers forming the repeating unit C include substituted or unsubstituted C2-4 olefins, One or more of the substituted groups are selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3.
[0039] In one example, the polymer microspheres are copolymers, which are formed by copolymerization of ethylene-vinyl acetate and one or more of the following compounds: polyethylene, polypropylene, polymethyl methacrylate, ethylene-propylene-diene copolymer, polyamide, polyester, polystyrene, polyacrylic acid-butadiene-styrene, polylactic acid, polyvinyl chloride, and polyvinyl butyral.
[0040] In one embodiment, the weight percentage of the repeating unit B (group -CH2-CH(OCOCH3)-) in the polymer microspheres is 4%-7%.
[0041] In one example, the weight percentage of the repeating unit A in the polymer microspheres is 50%-77% (eg, 50%, 55%, 60%, 65%, 70%, 75% or 77%).
[0042] In one embodiment, the weight proportion of the repeating unit A in the polymer microspheres is 61%-71%.
[0043] In one example, the weight percentage of the repeating unit C in the polymer microspheres is 20%-40% (eg, 20%, 25%, 30%, 35% or 40%).
[0044] In one embodiment, the weight percentage of the repeating unit C in the polymer microspheres is 25%-35%.
[0045] The weight ratio of repeating unit A, repeating unit B and repeating unit C in polymer microspheres can be obtained by thermogravimetric testing. Taking the weight ratio of repeating unit B in polymer microspheres as an example, the relationship between the mass of repeating unit B (group -CH2-CH(OCOCH3)-) and temperature is measured under programmed temperature control. The group -CH2-CH(OCOCH3)- undergoes thermal decomposition at temperatures above 250°C, and the weight loss of the polymer microspheres is the weight ratio of the group -CH2-CH(OCOCH3)-.
[0046] In one example, the weight proportion of repeating unit B (group -CH2-CH(OCOCH3)-) in the polymer microsphere is 3%-10%, the weight proportion of repeating unit A is 50%-77%, and the weight proportion of repeating unit C is 20%-40%. By controlling the weight proportions of repeating unit A, repeating unit B and repeating unit C within the above range, the melting point of the polymer microsphere can be made 80°C-140°C (for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 140°C) while reducing the swelling of the polymer microsphere in the electrolyte.
[0047] In one example, the weight proportion of the repeating unit B (group -CH2-CH(OCOCH3)-) in the polymer microspheres can be 4%-7%, the weight proportion of the repeating unit A is 61%-71%, and the weight proportion of the repeating unit C is 25%-35%. When the weight proportions of the repeating unit A, the repeating unit B, and the repeating unit C are controlled within the above range, the melting point of the polymer microspheres can be made 100°C-130°C while reducing the swelling of the polymer microspheres in the electrolyte.
[0048] The melting point of the polymer microspheres can be obtained by DSC testing.
[0049] In one example, the average particle size of the polymer microspheres is 0.01 μm-5 μm (for example, 0.01 μm, 0.05 μm, 0.1 μm, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm). Controlling the average particle size of the polymer microspheres within the above range can make the polymer microspheres absorb heat faster, shorten the distance for heat to be transferred from the surface of the polymer microspheres to the center, and improve the thermal conductivity efficiency of the polymer microspheres, thereby increasing the melting rate of the polymer microspheres, enabling the polymer microspheres to achieve rapid pore closure within 20 seconds, preventing lithium ion transmission, and avoiding thermal runaway of lithium ion batteries, thereby improving the safety performance of lithium ion batteries. When the average particle size of the polymer microspheres is greater than 5 μm, the specific surface area of the polymer microspheres is small, and the contact area with the environment (such as heat, solvent, etc.) is small. The time to trigger the melting of the polymer microspheres is long, and the distance for heat to be transferred from the surface of the polymer microspheres to the center is long, and the thermal conductivity efficiency is low, which is not conducive to the rapid pore closure of the diaphragm. When the average particle size of the polymer microspheres is less than 0.01 μm, the particle size of the polymer microspheres is too small and the melting speed is too fast. When the lithium-ion battery is in normal use, when the ambient temperature rises slightly, it is actually far from reaching the temperature of thermal runaway, and the polymer microspheres are prone to melt, thereby affecting the normal use of the lithium-ion battery.
[0050] In one example, the average particle size of the polymer microspheres is 0.3 μm-2 μm.
[0051] In the present invention, the average spherical particle size can be obtained by testing the following method: taking the average particle size of polymer microspheres as an example, water is used as a dispersant to disperse the polymer microsphere emulsion, and a laser particle size analyzer is used to test the polymer microsphere emulsion to obtain the average particle size of the polymer microspheres.
[0052] In one example, the number average molecular weight of the polymer microspheres is 20,000 Da-500,000 Da (e.g., 20,000 Da, 50,000 Da, 100,000 Da, 150,000 Da, 200,000 Da, 250,000 Da, 300,000 Da, 350,000 Da, 400,000 Da, 450,000 Da, or 500,000 Da).
[0053] In one example, the number average molecular weight of the polymer microspheres is 40,000 Da-360,000 Da.
[0054] In one example, the weight proportion of the group -CH2-CH(OCOCH3)- in the polymer microspheres can be 4%-7%, the weight proportion of the repeating unit A is 61%-71%, the weight proportion of the repeating unit C is 25%-35%, and the particle size of the polymer microspheres is 0.3μm-2μm, and the number average molecular weight of the polymer microspheres is 40000Da-360000Da.
[0055] In one example, the ratio of the weight proportion of the repeating unit B in the polymer microsphere to the average particle size of the polymer microsphere is 3-50 (for example, 3, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50). Controlling the ratio of the weight proportion of the repeating unit B in the polymer microsphere to the average particle size of the polymer microsphere within the above range can keep the melting temperature and melting speed of the polymer microsphere optimal, so that when the external temperature reaches the melting point of the polymer microsphere, the polymer microsphere can melt quickly and fill in the pores of the ceramic to form a relatively continuous polymer layer, blocking the migration of ions, enabling the diaphragm to achieve rapid thermal shutdown, preventing the rapid rise of the battery temperature, and improving the battery safety performance. When the weight ratio of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is less than 3, the average particle size of the polymer microspheres is large, resulting in a loose distribution of the polymer microspheres, making the thermal conductivity between the polymer microspheres poor. When the battery has thermal runaway, the continuous layer of the polymer microspheres after melting has poor density, resulting in a delay in the thermal shutdown temperature of the diaphragm, which reduces the safety performance of the battery. When the weight ratio of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is higher than 50, the average particle size of the polymer microspheres is too low, resulting in an overly dense distribution of the polymer microspheres, and the ionic conductivity of the diaphragm is low, which is not conducive to the migration of ions, resulting in poor high-rate charge and discharge performance of the battery.
[0056] In one example, the ratio of the weight percentage of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 6-25.
[0057] In one example, the weight proportion of the repeating unit B in the polymer microspheres is 3%-10%, the average particle size of the polymer microspheres is 0.01 μm-5 μm, and the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 3-50.
[0058] In one example, the weight proportion of the repeating unit B (group -CH2-CH(OCOCH3)-) in the polymer microspheres is 4%-7%, the average particle size of the polymer microspheres is 0.3μm-2μm, and the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 6-25.
[0059] In one example, the separator includes a substrate layer.
[0060] In one example, the thermal shrinkage rate of the substrate layer in the TD direction (105°C, 1 hour) is 0.5%-10% (for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%).
[0061] In the present invention, TD direction represents the width direction of the substrate layer, and the heat shrinkage rate in the TD direction can be tested by the following method: cut the substrate layer into a square with a side length of 70 cm, and mark the TD side (width direction) of the substrate layer, put it into an oven at 105°C and bake it for one hour, take it out and test the length of the TD side of the substrate layer x cm, and calculate (70-x) / 70, which is the heat shrinkage rate of the substrate layer in the TD direction (width direction) baked at 105°C for 1 hour.
[0062] In one example, the ratio of the weight proportion of the repeating unit B in the polymer microsphere to the shrinkage rate of the substrate layer in the TD direction (105°C, 1 hour) is 0.5-30 (0.5, 1, 5, 10, 15, 20, 25 or 30). By controlling the ratio of the weight proportion of the repeating unit B in the polymer microsphere to the shrinkage rate of the substrate layer in the TD direction (105°C, 1 hour) within the above range, the polymer microspheres can still maintain the coverage of the diaphragm on the negative electrode sheet when melted, thereby ensuring that after the lithium-ion battery is closed, the thermal runaway will not cause thermal shrinkage of the diaphragm to cause battery safety problems.
[0063] In one example, the ratio of the weight percentage of the repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer in the TD direction (105° C., 1 hour) is 2-10.
[0064] According to a specific embodiment, the weight proportion of the repeating unit B in the polymer microspheres is 3%-10%, the thermal shrinkage rate of the substrate layer in the TD direction (105°C, 1 hour) is 0.5%-10%, and the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer in the TD direction (105°C, 1 hour) is 0.5-30.
[0065] According to a specific embodiment, the weight proportion of the repeating unit B (group -CH2-CH(OCOCH3)-) in the polymer microspheres is 4%-7%, the thermal shrinkage rate of the substrate layer in the TD direction (105°C, 1 hour) is 0.5%-10%, and the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer in the TD direction (105°C, 1 hour) is 2-10.
[0066] In one example, the substrate layer comprises one or more of polyethylene (PE), polypropylene (PP), polyimide (PI), polyacrylonitrile and polyethersulfone.
[0067] In one example, the thickness of the substrate layer is 3 μm-20 μm (eg, 3 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm or 20 μm).
[0068] In the present invention, the thickness can be obtained by SEM cross-section observation test. For example, the thickness of the substrate layer can be measured by observing the cross section of the diaphragm through SEM and measuring the thickness of the substrate layer in the cross section.
[0069] In one example, the pore size of the substrate layer is 0.02 μm-0.5 μm (eg, 0.02 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm or 0.5 μm).
[0070] In one example, the diaphragm further includes a ceramic layer, a polymer microsphere layer and a glue layer.
[0071] In one example, the composition of the adhesive layer includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene modified and its copolymer, polyacrylonitrile, polymethyl methacrylate, polyacrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol and its copolymer-modified polyvinyl alcohol, polyvinyl acetate, polyacrylamide, phenolic resin, epoxy resin, water-based polyurethane, ethylene-vinyl acetate copolymer, polyacrylic acid copolymer, lithium polystyrene sulfonate, pure benzene latex, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyvinyl pyrrolidone, polyethylene oxide, cellulose acetate, butyl cellulose, propyl cellulose, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose and cyanoethyl sucrose.
[0072] In one example, the thickness of the glue layer is 0.1 μm-10 μm (eg, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm).
[0073] In one example, the composition of the polymer microsphere layer includes the polymer microspheres.
[0074] In one example, the thickness of the polymer microsphere layer is 1 μm-3 μm.
[0075] In one example, the polymer microsphere layer further includes a third binder and a third auxiliary agent.
[0076] In one example, the third binder includes polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth) acrylate, aramid resin, poly (meth) acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate, carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), carboxyethyl cellulose, polyacrylamide, phenolic resin, epoxy resin, water-based polyurethane, ethylene-vinyl acetate copolymer, polyacrylic copolymer, lithium polystyrene sulfonate, water-based silicone resin, nitrile-polyvinyl chloride blend, styrene acrylic latex and pure styrene latex and one or more combinations of blends and copolymers derived from the modified aforementioned polymers.
[0077] In one example, the first auxiliary agent includes at least one of multi-branched alcohol, triethyl phosphate, polyethylene glycol, fluorinated polyethylene oxide, polyethylene oxide, stearic acid, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfonate, fatty acid glyceride, sorbitan fatty acid ester and polysorbate.
[0078] In one example, in the polymer microsphere layer, the weight content of the polymer microspheres is 70%-98% (e.g., 70%, 75%, 80%, 85%, 90%, 95% or 98%), the weight content of the third binder is 1.8%-22% (e.g., 1.8%, 2%, 5%, 10%, 15%, 20% or 22%), and the weight content of the third auxiliary agent is 0.2%-8% (e.g., 0.2%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%).
[0079] In one example, in the polymer microsphere layer, the weight content of the polymer microsphere is 80%-95%, the weight content of the third binder is 4.5%-15%, and the weight content of the third auxiliary agent is 0.5%-5%.
[0080] In one example, the ceramic layer comprises first inorganic particles, a first binder, and a first auxiliary agent.
[0081] In one example, the first inorganic particles include at least one of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, nickel oxide, and zeolite.
[0082] In one example, the zeolite includes solid particles and / or particles having a hierarchical pore structure.
[0083] In one example, the configuration of the zeolite includes one or more of MEI, BEA, RRD, STT, MWW, MFI, LTA, FAU, SOD, CHA and MOR.
[0084] In one example, the average particle size of the first inorganic particles is 0.01 μm-10 μm (for example, 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm).
[0085] In one example, the first binder includes polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth)acrylate, aramid resin, poly (meth)acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate, carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), carboxyethyl cellulose, polyacrylamide, phenolic resin, epoxy resin, water-based polyurethane, ethylene-vinyl acetate copolymer, polyacrylic copolymer, lithium polystyrene sulfonate, water-based silicone resin, nitrile-polyvinyl chloride blend, styrene-acrylic latex and pure styrene latex and one or more combinations of blends and copolymers derived from the modified aforementioned polymers.
[0086] In one example, the first auxiliary agent includes at least one of multi-branched alcohol, triethyl phosphate, polyethylene glycol, fluorinated polyethylene oxide, polyethylene oxide, stearic acid, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfonate, fatty acid glyceride, sorbitan fatty acid ester and polysorbate.
[0087] In one example, based on the total weight of the ceramic layer, the weight content of the first inorganic particles is 70%-94% (for example, 80%, 83%, 85%, 88%, 90%, 93% or 94%), the weight content of the first binder is 1%-25% (for example, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23% or 25%), and the weight content of the first auxiliary agent is 0.8%-5% (for example, 0.8%, 1%, 2%, 3%, 4% or 5%).
[0088] In one example, based on the total weight of the ceramic layer, the weight content of the first inorganic particles is 80%-95%, the weight content of the first binder is 4%-15%, and the weight content of the first auxiliary agent is 1%-5%.
[0089] In one example, the ceramic layer is located on one side of the substrate layer, the adhesive layer is located on the surface of the substrate layer and the ceramic layer, the polymer microsphere layer is located between the substrate layer and the ceramic layer, and / or the polymer microsphere layer is located between the substrate layer and the adhesive layer, and / or the polymer microsphere layer is located between the ceramic layer and the adhesive layer.
[0090] like Figure 1As shown, the ceramic layer 2 is located on one side of the substrate layer 1, the adhesive layer 3 is located on the surface of the substrate layer 1 and the ceramic layer 2, the polymer microsphere layer 4 is located between the substrate layer 1 and the ceramic layer 2, the ceramic layer 2 includes inorganic particles 21, and the polymer microsphere layer 4 includes polymer microspheres 41.
[0091] like Figure 2 As shown, before the lithium-ion battery undergoes thermal runaway, the polymer microspheres in the polymer microsphere layer 4 melt, seal the pores of the diaphragm, prevent lithium ion transmission, and avoid thermal runaway of the lithium-ion battery, thereby improving the safety performance of the lithium-ion battery.
[0092] like Figure 3 As shown, the ceramic layer 2 is located on one side of the substrate layer 1, the adhesive layer 3 is located on the surface of the substrate layer 1 and the ceramic layer 2, the polymer microsphere layer 4 is located between the ceramic layer 2 and the adhesive layer 3, the ceramic layer 2 includes inorganic particles 21, and the polymer microsphere layer 4 includes polymer microspheres 41.
[0093] In one example, the ceramic layer is located on both sides of the substrate layer, the adhesive layer is located on the surface of the ceramic layer, the polymer microsphere layer is located between the ceramic layer and the substrate layer, and / or the polymer microsphere layer is located between the ceramic layer and the adhesive layer.
[0094] like Figure 4 As shown, the ceramic layer 2 is located on both sides of the substrate layer 1, the adhesive layer 3 is located on the surface of the ceramic layer 2, the polymer microsphere layer 4 is located between the ceramic layer 2 and the substrate layer 1, the ceramic layer 2 includes inorganic particles 21, and the polymer microsphere layer 4 includes polymer microspheres 41.
[0095] like Figure 5 As shown, the ceramic layer 2 is located on both sides of the substrate layer 1, the adhesive layer 3 is located on the surface of the ceramic layer 2, the polymer microsphere layer 4 is located between the ceramic layer 2 and the adhesive layer 3, the ceramic layer 2 includes inorganic particles 21, and the polymer microsphere layer 4 includes polymer microspheres 41.
[0096] A polymer microsphere layer is set in the diaphragm. Through the regulating effect of the polymer microspheres, the behavior of the diaphragm at high temperature can be finely controlled, so that the polymer microsphere layer can undergo a volume change at the melting temperature of the polymer microspheres, thereby effectively blocking the pores between the first inorganic particles, preventing the transmission of lithium ions, avoiding the risk of thermal runaway of lithium-ion batteries, and improving the safety performance of lithium-ion batteries.
[0097] In another example, the diaphragm further includes a composite layer and an adhesive layer, wherein the composite layer is located on one side or both sides of the substrate layer, the adhesive layer is located on the surface of the substrate layer and / or the surface of the composite layer, and the components of the composite layer include second inorganic particles and polymer microspheres.
[0098] like Figure 6 As shown, the diaphragm includes a substrate layer 1, a composite layer 5 located on one side of the substrate layer 1, and a glue layer located on the surfaces of the substrate layer 1 and the composite layer 5. The components of the composite layer 5 include second inorganic particles 53 and polymer microspheres 41.
[0099] like Figure 7 As shown, before the lithium-ion battery undergoes thermal runaway, the polymer microspheres in the composite layer 5 melt to form a ceramic polymer dense layer 6, which can seal the pores of the diaphragm, prevent lithium ion transmission, and avoid thermal runaway of the lithium-ion battery, thereby improving the safety performance of the lithium-ion battery.
[0100] By blending the second inorganic particles with polymer microspheres to form a composite coating, the behavior of the diaphragm at high temperature can be more finely controlled through the regulation of the polymer microspheres, so that the composite layer can undergo a volume change at the melting temperature of the polymer microspheres, thereby effectively blocking the pores between the second inorganic particles and forming a dense layer of ceramic polymers, and the polymer microspheres are mixed into the original ceramic layer to form a composite coating. The advantages of the original ceramic layer such as hardness, wear resistance and corrosion resistance are retained in the composite coating. At the same time, the addition of polymer microspheres brings additional toughness and impact resistance, thereby improving the comprehensive mechanical properties of the composite coating. In addition, polymer microspheres also help to improve the interface bonding between the second inorganic particles and the substrate, and improve the adhesion and durability of the composite coating. Although a pure polymer microsphere layer can already enable the diaphragm to achieve the function of thermal shutdown, compared with a pure polymer microsphere layer, the composite layer can give the diaphragm a thermal shutdown function by adding only a small amount of polymer microspheres without changing the overall thickness of the diaphragm, providing more space for lithium-ion batteries to increase the energy density of the battery.
[0101] In one example, the second inorganic particles include at least one of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, nickel oxide, and zeolite.
[0102] In one example, the zeolite includes solid particles and / or particles having a hierarchical pore structure.
[0103] In one example, the configuration of the zeolite includes one or more of MEI, BEA, RRD, STT, MWW, MFI, LTA, FAU, SOD, CHA and MOR.
[0104] In one example, based on the total weight of the composite layer, the weight content of the polymer microspheres is 5%-40% (for example, 5%, 10%, 15%, 20%, 25% or 30%), and the weight content of the second inorganic particles is 50%-90% (for example, 60%, 65%, 70%, 75%, 80%, 85% or 90%).
[0105] In one example, based on the total weight of the composite layer, the weight content of the polymer microspheres is 10%-30%, and the weight content of the second inorganic particles is 65%-80%.
[0106] In one example, the composite layer further includes a second binder and a second auxiliary agent.
[0107] In one example, the second binder includes polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth)acrylate, aramid resin, poly (meth)acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate, carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), carboxyethyl cellulose, polyacrylamide, phenolic resin, epoxy resin, water-based polyurethane, ethylene-vinyl acetate copolymer, polyacrylic copolymer, lithium polystyrene sulfonate, water-based silicone resin, nitrile-polyvinyl chloride blend, styrene-acrylic latex and pure styrene latex and one or more combinations of blends and copolymers derived from the modified aforementioned polymers.
[0108] In one example, the second auxiliary agent includes at least one of multi-branched alcohol, triethyl phosphate, polyethylene glycol, fluorinated polyethylene oxide, polyethylene oxide, stearic acid, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfonate, fatty acid glyceride, sorbitan fatty acid ester and polysorbate.
[0109] In one example, based on the total weight of the composite layer, the weight content of the second binder is 1%-10% (for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%), and the weight content of the second auxiliary agent is 0%-10% (for example, 0%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%).
[0110] In the composite layer, the second auxiliary agent may be present or absent. When the weight content of the auxiliary agent in the composite layer is 0%, it means that the second auxiliary agent does not exist.
[0111] In one example, based on the total weight of the composite layer, the weight content of the second binder is 4%-8%, and the weight content of the second auxiliary agent is 0%-2%.
[0112] In one example, the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 1-10 (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10). Controlling the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres within the above range can ensure that the diaphragm is completely closed at the melting point temperature of the polymer microspheres, thereby ensuring that ion migration is effectively blocked and further exothermic reactions of the battery are inhibited, thereby avoiding thermal runaway of the battery. When the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is less than 2, the thickness of the composite layer is too thin or the average particle size of the polymer microspheres is too large. When the thickness of the composite layer is too thin, it is impossible to provide enough material to completely close the pores, resulting in that after the polymer microspheres melt at the melting point temperature, all pores of the diaphragm cannot be closed, and some ions can still migrate through the unclosed pores, thereby continuing to drive the exothermic reaction of the battery and reducing the safety performance of the battery. When the average particle size of the polymer microspheres is too large, the distribution of the polymer microspheres in the composite layer is relatively sparse, resulting in the inability to form a continuous network after the polymer microspheres melt. When the thickness of the composite layer is greater than 10 and the average particle size of the polymer microspheres is greater than 10, the thickness of the composite layer is too thick or the average particle size of the polymer microspheres is too small. When the thickness of the composite layer is too thick, although the closed-pore effect can be ensured, the normal transmission efficiency of the ions will be affected, the rate performance of the battery will be reduced, and the weight and cost of the battery will be increased. When the average particle size of the polymer microspheres is too small, although the closed-pore effect can be ensured, the normal transmission efficiency of the ions will be affected, resulting in poor rate performance of the battery.
[0113] In one example, the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 3-8.
[0114] In one example, the composite layer has a thickness of 0.5 μm-10 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).
[0115] In one example, the average particle size of the second inorganic particles is 0.1 μm-10 μm (eg, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm).
[0116] In one example, the ratio of the particle size of the second inorganic particles to the average particle size of the polymer microspheres is 2-10 (e.g., 2, 3, 4, 5, 6, 7, 8, 9 or 10). Controlling the ratio of the particle size of the second inorganic particles to the particle size of the polymer microspheres within the above range can enable the diaphragm to achieve rapid pore closure within 20 seconds.
[0117] In one example, the ratio of the particle size of the second inorganic particles to the particle size of the polymer microspheres is 3.5-7.
[0118] In one example, in an oven at 136° C., the air permeability of the membrane is higher than 10000 s / 100 cc within no more than 10 min (e.g., 10 min, 9 min, 8 min, 7 min, 6 min, 5 min, 4 min, 3 min, 2 min, or 1 min), indicating that the polymer microspheres in the membrane can effectively achieve melt closure, thereby blocking the pores of the membrane and significantly reducing the permeation path.
[0119] In one example, the membrane is placed in a propylene carbonate (PC) solvent at 136° C., and the air permeability of the membrane is higher than 6000 s / 100 cc within no more than 5 min (e.g., 5 min, 4 min, 3 min, 2 min, or 1 min), indicating that the polymer microspheres in the membrane can effectively achieve melt closure, thereby blocking the pores of the membrane and significantly reducing the permeation path.
[0120] In the present invention, the specific test method of the air permeability value is: take 6.45cm 2 For the diaphragm (after baking or PC bath treatment), under the pressure of 1.21KPa, the time for 100ml of air to pass through the diaphragm is the air permeability value.
[0121] A second aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the separator according to the first aspect of the present invention.
[0122] The materials of the lithium-ion battery except the separator can be prepared according to the methods in the art, and can achieve the effects of higher cycle stability and higher safety performance.
[0123] In one example, in a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is lower than 136°C. This indicates that the battery is closed after 136°C, achieving a thermal shutdown function, thereby preventing the lithium-ion battery from experiencing thermal runaway behavior.
[0124] In one example, the lithium-ion battery further includes a negative electrode sheet, a positive electrode sheet and an electrolyte.
[0125] The negative electrode sheet may be a conventional negative electrode sheet in the art, for example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a negative electrode conductor and a negative electrode binder.
[0126] In one example, the negative electrode active material includes a graphite mixed material and / or graphite doped with at least one of hard carbon, soft carbon, silicon oxide and silicon carbon.
[0127] In one example, the negative electrode active material is a graphite mixed material doped with hard carbon, wherein the weight content of the hard carbon is 2wt%-10wt% (for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%) based on the total weight of the graphite mixed material.
[0128] In one example, based on the total weight of the graphite mixed material, the weight content of the hard carbon is 3wt%-5wt%.
[0129] In one example, the negative electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber and carbon nanotube.
[0130] In one example, the negative electrode binder includes one or more of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, polyethylene oxide, and polyvinylidene fluoride.
[0131] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 80wt%-99.5wt% (for example, 80wt%, 85wt%, 90wt%, 95wt%, 99wt%, 99.5wt%), the weight content of the negative electrode conductor is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%), and the weight content of the negative electrode binder is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%).
[0132] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 90wt%-99wt%, the weight content of the negative electrode conductor is 0.5wt%-5wt%, and the weight content of the negative electrode binder is 0.5wt%-5wt%.
[0133] In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, a positive electrode conductor and a positive electrode binder.
[0134] In one example, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate and lithium manganese iron phosphate.
[0135] In one example, the positive electrode conductive agent includes one or more of carbon nanotubes and carbon black.
[0136] In one example, the positive electrode binder includes one or more of polyvinylidene fluoride, acrylic acid-modified polyvinylidene fluoride, carboxylic acid-modified polyvinylidene fluoride, polyacrylic acid, polyacrylic acid copolymer, polymethyl methacrylate, and polyimide.
[0137] In one example, in one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 88wt%-98wt% (for example, 88wt%, 90wt%, 92wt%, 95wt% or 98wt%), the weight content of the positive electrode conductor is 1wt%-6wt% (for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or 6wt%), and the weight content of the positive electrode binder is 1wt%-6wt% (for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or 6wt%).
[0138] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 94.5wt%-97.5wt%, the weight content of the positive electrode conductor is 2wt%-5wt%, and the weight content of the positive electrode binder is 1.5wt%-4wt%.
[0139] In one example, the electrolyte includes a lithium salt, an organic solvent, and an additive.
[0140] In one example, the lithium salt includes one of lithium hexafluorophosphate (LiPF6), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB) and lithium tetrafluoroborate (LiBF4).
[0141] In one example, the organic solvent includes a mixture of one or more of diethyl carbonate (DEC), ethylene carbonate (EC), propyl propionate, ethyl propionate, ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and propylene carbonate (PC).
[0142] In one example, the additive includes one or more of fluoroethylene carbonate, vinylene carbonate (VC), 1,3-propane sultone (PS), 1,3-acrylonitrile lactone (PST), vinyl ethylene carbonate (VEC), succinonitrile (SN) and 1,3,6-hexanetrinitrile (HTCN).
[0143] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 5%-25% (for example, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 23% or 25%), the weight content of the organic solvent is 70%-88% (for example, 70%, 73%, 75%, 78%, 80%, 83%, 85% or 88%), and the weight content of the additive is 3%-20% (for example, 3%, 5%, 8%, 10%, 13%, 15%, 18% or 20%).
[0144] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 7%-20%, the weight content of the organic solvent is 75%-85%, and the weight content of the additive is 5%-18%.
[0145] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0146] The following examples are provided to illustrate the separator and battery of the present invention.
[0147] Example Group I is used to illustrate a diaphragm in which polymer microspheres are located in a composite layer.
[0148] Example I-1
[0149] (1) Diaphragm
[0150] Component preparation: substrate layer: polyethylene (PE), the thickness of the substrate layer is 5 μm, and the heat shrinkage rate in the TD direction is 2.3%;
[0151] Composite layer: Second inorganic particles: Alumina (average particle size 3 μm), 68 parts by weight, polymer microspheres: EVA-PVC copolymer (the molecular formula of the polymer microspheres is [CH2-CH2] x -[CH2-CH(OCOCH3)] y -[CH2-CHCl] z , wherein the weight proportion of repeating unit B (-CH2-CH(OCOCH3)-) is 6%, the weight proportion of repeating unit A (-CH2-CH2-) is 64%, and the weight proportion of repeating unit C (-CH2-CHCl-) is 30%; the number average molecular weight of the polymer microspheres is 314230Da, the average particle size is 0.8μm, and the melting point is 120℃), 25 parts by weight, the second binder: polyvinylidene fluoride-hexafluoropropylene, 6 parts by weight, the second auxiliary agent: polyethylene glycol, 1 part by weight; the thickness of the composite layer is 5μm;
[0152] Adhesive layer: polyvinylidene fluoride-hexafluoropropylene, the thickness of the adhesive layer is 1 μm.
[0153] The second inorganic particles, polymer microspheres, the second binder and the second auxiliary agent are added to 860 parts of DMAC, and mixed evenly to obtain a mixed slurry. The mixed slurry is coated on one side of the diaphragm substrate layer by micro-gravure to form a composite layer. After drying, a glue layer is coated on the surface of the composite layer and the other side of the substrate layer, respectively.
[0154] Among them, the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is: 6 / 0.8=7.5; the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is: 5 / 0.8=6.25; the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is: 3 / 0.8=3.75; the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer is: 6 / 2.3=2.61; in an oven at 136°C, the air permeability of the diaphragm is 18350s / 100cc within no more than 10 minutes.
[0155] (2) Positive electrode
[0156] Positive electrode active material: lithium nickel cobalt manganese oxide, 96 parts by weight;
[0157] Positive electrode conductive agent: carbon black, 2.5 parts by weight;
[0158] Positive electrode binder: polyvinylidene fluoride, 1.5 parts by weight.
[0159] The positive electrode active material, positive electrode conductor, positive electrode binder and solvent N-methylpyrrolidone (NMP) are uniformly mixed to obtain positive electrode slurry, and the positive electrode slurry is uniformly coated on the surfaces of both sides of the positive electrode collector to form a positive electrode active material layer. The coated positive electrode sheet is baked to obtain the positive electrode sheet.
[0160] (3) Negative electrode
[0161] Negative electrode active material: 96 parts by weight of a graphite mixed material with hard carbon (wherein the weight ratio of graphite to hard carbon is 97:3);
[0162] Negative electrode conductive agent: conductive carbon black, 1.5 parts by weight;
[0163] Negative electrode binder: sodium carboxymethyl cellulose (CMC-Na), 1 part by weight, 1.5 parts by weight of styrene-butadiene latex.
[0164] The negative electrode active material, negative electrode binder, negative electrode binder and negative electrode conductive agent are mixed, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on both sides of the high-strength carbon-coated copper foil, and after drying at room temperature, it is transferred to an oven at 80°C for drying for 10 hours, and then rolled and cut to obtain a negative electrode sheet.
[0165] (4) Electrolyte
[0166] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), mix the organic solvent evenly, then quickly add fully dried lithium salt, add additives, stir for 10 hours to fully dissolve, and the desired electrolyte can be obtained. Among them, lithium salt: lithium hexafluorophosphate, 15 parts by weight; organic solvent: 75 parts by weight, wherein the weight ratio of ethylene carbonate, propylene carbonate, propyl propionate, and ethyl propionate is 15:15:50:20; additives: 2 parts by weight of 1,3-propane sultone, 3 parts by weight of 1,3,6-hexane trinitrile, and 5 parts by weight of fluoroethylene carbonate, a total of 10 parts by weight.
[0167] (5) Preparation of lithium ions
[0168] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step (3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. In the temperature rise test of 1°C / min, the temperature at which the internal resistance of the lithium ion battery exceeds 1000Ω is 125°C.
[0169] Example I-2
[0170] The method is carried out in accordance with Example I-1, except that the preparation of the diaphragm is specifically as follows:
[0171] Component preparation: substrate layer: polyimide (PI), the thickness of the substrate layer is 5 μm, and the thermal shrinkage rate in the TD direction is 1.4%;
[0172] Composite layer: Second inorganic particles: Alumina (average particle size 8 μm), 64.5 parts by weight, polymer microspheres: EVA-PVC copolymer (the molecular formula of the polymer microspheres is [CH2-CH2] x -[CH2-CH(OCOCH3)] y -[CH2-CHCl] z, wherein the weight proportion of repeating unit B (-CH2-CH(OCOCH3)-) is 3.2%, the weight proportion of repeating unit A (-CH2-CH2-) is 75%, and the weight proportion of repeating unit C (-CH2-CHCl-) is 21.8%; the number average molecular weight of the polymer microspheres is 402980Da, the average particle size is 1μm, and the melting point is 140°C), 33 weight parts, the second binder: polyvinylidene fluoride-hexafluoropropylene, 2 weight parts; the second auxiliary agent: polyethylene glycol, 0.5 weight part; the thickness of the composite layer is 9μm;
[0173] Adhesive layer: polyvinylidene fluoride-hexafluoropropylene, the thickness of the adhesive layer is 1 μm.
[0174] The second inorganic particles, polymer microspheres, the second binder and the second auxiliary agent are added to 860 parts of DMAC, and mixed evenly to obtain a mixed slurry. The mixed slurry is coated on one side of the diaphragm substrate layer by micro-gravure to form a composite layer. After drying, a glue layer is coated on the surface of the composite layer and the other side of the substrate layer, respectively.
[0175] Among them, the ratio of the weight proportion of repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 3.2; the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 9; the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 8; the ratio of the weight proportion of repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer is 2.29; in an oven at 136°C, the air permeability of the diaphragm is 31024s / 100cc within no more than 10 minutes.
[0176] In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 146°C.
[0177] Example I-3 Group
[0178] This group of examples is used to illustrate the effects produced when the total content of repeating unit B in the polymer microspheres changes.
[0179] Example I-3a
[0180] Refer to Example I-1, except that the weight content of repeating unit B in the polymer microspheres is 4%, the weight content of repeating unit A is 65%, the weight content of repeating unit C is 31%, the number average molecular weight of the corresponding polymer microspheres is 351620Da, the melting point of the polymer microspheres is 130°C, the ratio of the weight proportion of repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 5, the ratio of the weight proportion of repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer is 1.74, and in an oven at 136°C, the air permeability of the diaphragm is 13147s / 100cc within no more than 10min; in a temperature rise test of 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 133°C.
[0181] Example I-3b
[0182] Refer to Example I-1, except that the weight content of repeating unit B in the polymer microspheres is 7%, the weight content of repeating unit A is 63.5%, the weight content of repeating unit C is 29.5%, the number average molecular weight of the corresponding polymer microspheres is 183280Da, the melting point of the polymer microspheres is 100°C, the ratio of the weight proportion of repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 8.75, the ratio of the weight proportion of repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer is 3.04, and in an oven at 136°C, the air permeability of the diaphragm is 23349s / 100cc within no more than 10min; in a temperature rise test of 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 107°C.
[0183] Example I-3c
[0184] The process is carried out in accordance with Example I-1, except that the weight content of the repeating unit B in the polymer microspheres is 10%, the weight content of the repeating unit A is 62%, the weight content of the repeating unit C is 28%, the number average molecular weight of the corresponding polymer microspheres is 103270Da, the melting point of the polymer microspheres is 80°C, the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 12.5, the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer is 4.35, and in an oven at 136°C, the air permeability of the diaphragm is 25143s / 100cc within no more than 10min; in a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 86°C.
[0185] Example I-4 Group
[0186] This group of examples is used to illustrate the effects produced when the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is changed.
[0187] Example I-4a
[0188] Refer to Example I-1, except that the average particle size of the polymer microspheres is 1.9 μm, the thickness of the composite layer is 6 μm, the ratio of the weight proportion of the repeating unit B in the corresponding polymer microspheres to the average particle size of the polymer microspheres is 3.16; the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 3.16; the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 1.58; in an oven at 136°C, the air permeability of the diaphragm is 56240s / 100cc within no more than 10 min.
[0189] Example I-4b
[0190] Refer to Example I-1, except that the average particle size of the polymer microspheres is 0.13 μm, the thickness of the composite layer is 1 μm, the average particle size of the second inorganic particles is adjusted to 0.5 to match the thickness of the composite layer, and the ratio of the weight proportion of the corresponding polymer microspheres to the average particle size of the polymer microspheres is 46.15; the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 7.69; the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 3.85; in an oven at 136°C, the air permeability of the diaphragm is 42351s / 100cc within no more than 10 min.
[0191] Example I-4c
[0192] Refer to Example I-1, except that the average particle size of the polymer microspheres is 4.5 μm, the thickness of the composite layer is 6 μm, the ratio of the weight proportion of the repeating unit B in the corresponding polymer microspheres to the average particle size of the polymer microspheres is 1.33; the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 1.33; the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 0.67; in an oven at 136°C, the air permeability of the diaphragm is 11003s / 100cc within no more than 10 min.
[0193] Example I-4d
[0194] Refer to Example I-1, except that the average particle size of the polymer microspheres is 5.4 μm, the thickness of the composite layer is 10 μm, the ratio of the weight proportion of the repeating unit B in the corresponding polymer microspheres to the average particle size of the polymer microspheres is 1.11; the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 1.85; the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 0.56; in an oven at 136°C, the air permeability of the diaphragm is 58640s / 100cc within no more than 10 min.
[0195] Example I-4e
[0196] Refer to Example I-1, except that the thickness of the composite layer is 6 μm, and the corresponding ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 7.5; in an oven at 136°C, the air permeability of the diaphragm is 55270 s / 100 cc within no more than 10 min.
[0197] Example I-4f
[0198] Refer to Example I-1, except that the thickness of the composite layer is 8 μm, and the corresponding ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 10; in an oven at 136°C, the air permeability of the diaphragm is 69138 s / 100 cc within no more than 10 min.
[0199] Example I-4g
[0200] Refer to Example I-1, except that the thickness of the composite layer is 10 μm, and the corresponding ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 12.5; in an oven at 136°C, the air permeability of the diaphragm is 76351s / 100cc within no more than 10 minutes.
[0201] Example I-5 Group
[0202] This group of examples is used to illustrate the effects produced when the weight content of polymer microspheres in the composite layer is changed.
[0203] Example I-5a
[0204] Refer to Example I-1, except that the weight content of the polymer microspheres in the composite layer is 10%, the second inorganic particles: aluminum oxide (average particle size is 3 μm), 83 parts by weight, in order to achieve the above-mentioned corresponding changes in weight content, the average particle size of the polymer microspheres is 0.5 μm, the ratio of the weight share of repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 12, the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 10, the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 6, and the air permeability of the diaphragm is 13637s / 100cc within no more than 10 minutes in an oven at 136°C.
[0205] Example I-5b
[0206] Refer to Example I-1, except that the weight content of the polymer microspheres in the composite layer is 5%, the second inorganic particles: aluminum oxide (average particle size is 1 μm), 88 parts by weight, in order to achieve the above-mentioned corresponding changes in weight content, the average particle size of the polymer microspheres is 0.3 μm, the ratio of the weight share of repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 20, the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 16.67, the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 10, and in an oven at 136°C, the air permeability of the diaphragm is 12920s / 100cc within no more than 10 minutes.
[0207] Example I-5c
[0208] Refer to Example I-1, except that the weight content of the polymer microspheres in the composite layer is 35%, and the second inorganic particles: aluminum oxide (average particle size is 3 μm), 58 weight parts; in an oven at 136°C, the air permeability of the diaphragm is 66310s / 100cc within no more than 10 minutes.
[0209] Example I-5d
[0210] Refer to Example I-1, except that the weight content of the polymer microspheres in the composite layer is 43%, the second inorganic particles: aluminum oxide (average particle size of 3 μm), 50 parts by weight, in an oven at 136°C, the air permeability of the diaphragm is 86750s / 100cc within no more than 10 minutes.
[0211] Example I-6 Group
[0212] This group of examples is used to illustrate the influence produced when the average particle size of the second inorganic particles is changed.
[0213] Example I-6a
[0214] Refer to Example I-1, except that the average particle size of the second inorganic particles is 4.5 μm, and the ratio of the corresponding average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 5.63; in an oven at 136°C, the air permeability of the diaphragm is 22237 s / 100cc within no more than 10 min.
[0215] Example I-6b
[0216] Refer to Example I-1, except that the average particle size of the second inorganic particles is 0.5 μm, and the ratio of the corresponding average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 0.63; in an oven at 136°C, the air permeability of the diaphragm is 49483 s / 100cc within no more than 10 min.
[0217] Example I-6c
[0218] Refer to Example I-1, except that the average particle size of the second inorganic particles is 7 μm. In order to allow the composite layer to accommodate the second inorganic particles of the above average particle size and reduce the influence of the change in the thickness of the composite layer on the air permeability of the diaphragm, the thickness of the composite layer is changed to 8 μm accordingly. The ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 10, and the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 8.75. In an oven at 136°C, the air permeability of the diaphragm is 88542s / 100cc within no more than 10 minutes.
[0219] Example I-6d
[0220] Refer to Example I-1, except that the average particle size of the second inorganic particles is 10 μm. In order to allow the composite layer to accommodate the second inorganic particles of the above average particle size and reduce the influence of the change in the thickness of the composite layer on the air permeability of the diaphragm, the thickness of the composite layer is changed to 12 μm accordingly. The ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 15, and the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 12.5. In an oven at 136°C, the air permeability of the diaphragm is 89116s / 100cc within no more than 10 minutes.
[0221] Example I-7 Group
[0222] This group of examples is used to illustrate the impact produced when the thermal shrinkage rate of the substrate layer changes.
[0223] Example I-7a
[0224] Refer to Example I-1, except that the thermal shrinkage rate of the substrate layer is 0.9%. In order to achieve the above thermal shrinkage rate, the substrate layer is adjusted to PI, and the ratio of the weight proportion of the corresponding polymer microspheres repeating unit B to the thermal shrinkage rate of the substrate layer in the TD direction is 6.67. In an oven at 136°C, the air permeability of the diaphragm is 16385s / 100cc within no more than 10min.
[0225] Example I-7b
[0226] Refer to Example I-1, except that the thermal shrinkage of the substrate layer is 8%, the ratio of the weight proportion of the corresponding polymer microspheres repeating unit B to the thermal shrinkage of the substrate layer in the TD direction is 0.75, and the air permeability of the diaphragm is 23050s / 100cc in an oven at 136°C for no more than 10 minutes.
[0227] Example I-7c
[0228] Refer to Example I-1, except that the thermal shrinkage rate of the substrate layer is 1.3%. In order to achieve the above thermal shrinkage rate, the substrate layer is adjusted to PI, and the ratio of the weight proportion of the corresponding polymer microspheres repeating unit B to the thermal shrinkage rate of the substrate layer in the TD direction is 4.62. In an oven at 136°C, the air permeability of the diaphragm is 36635s / 100cc within no more than 10min.
[0229] Example I-7d
[0230] Refer to Example I-1, except that the thermal shrinkage rate of the substrate layer is 0.7%. In order to achieve the above thermal shrinkage rate, the substrate layer is adjusted to PI, and the ratio of the weight proportion of the corresponding polymer microspheres repeating unit B to the thermal shrinkage rate of the substrate layer in the TD direction is 8.57. In an oven at 136°C, the air permeability of the diaphragm is 15527s / 100cc within no more than 10 minutes.
[0231] Example I-7e
[0232] Refer to Example I-1, except that the thermal shrinkage rate of the substrate layer is 0.22%. In order to achieve the above thermal shrinkage rate, the substrate layer is adjusted to PI, and the ratio of the weight share of the corresponding polymer microspheres repeating unit B to the thermal shrinkage rate of the substrate layer in the TD direction is 27.27. In an oven at 136°C, the air permeability of the diaphragm is 14580s / 100cc within no more than 10min.
[0233] Example I-7f
[0234] Refer to Example I-1, except that the thermal shrinkage of the substrate layer is 3.2%, the ratio of the weight proportion of the corresponding polymer microspheres repeating unit B to the thermal shrinkage of the substrate layer in the TD direction is 1.88, and the air permeability of the diaphragm is 20358s / 100cc in an oven at 136°C for no more than 10 minutes.
[0235] Example I-8 Group
[0236] This group of examples is used to illustrate the effects produced when the repeating unit A is changed.
[0237] Example I-8a
[0238] Refer to Example I-1, except that the repeating unit A is -CH2-CH2-CH2-, the corresponding number average molecular weight of the polymer microspheres is 325140Da, the melting point of the polymer microspheres is 123°C, and the air permeability of the diaphragm is 26280s / 100cc in an oven at 136°C for no more than 10min. In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 128°C.
[0239] Example I-8b
[0240] Refer to Example I-1, except that the repeating unit A is MMA (-CH2-CH3OCO(CH3)-), the number average molecular weight of the corresponding polymer microspheres is 296730 Da, the melting point of the polymer microspheres is 125°C, and the air permeability of the diaphragm is 21547s / 100cc in an oven at 136°C for no more than 10 min. In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 129°C.
[0241] Example I-8c
[0242] The same method as in Example I-1 is carried out except that the repeating unit A is a vinyl methyl ether group. The number average molecular weight of the corresponding polymer microspheres is 303570Da, the melting point of the polymer microspheres is 121°C, and the air permeability of the diaphragm is 13133s / 100cc within no more than 10min in an oven at 136°C. In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 126°C.
[0243] Example I-9 Group
[0244] This group of examples is used to illustrate the effects produced when the repeating unit C is changed.
[0245] Example I-9a
[0246] Refer to Example I-1, except that the repeating unit C is -CH2-CH2-, the corresponding number average molecular weight of the polymer microspheres is 289460Da, the melting point of the polymer microspheres is 120°C, and the air permeability of the diaphragm is 19248s / 100cc within no more than 10min in an oven at 136°C. In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 125°C.
[0247] Example I-9b
[0248] Refer to Example I-1, except that the repeating unit C is an acrylic acid group (-CH2-CH(COOH)-), the number average molecular weight of the corresponding polymer microspheres is 317350Da, the melting point of the polymer microspheres is 124°C, and the air permeability of the diaphragm is 31220s / 100cc within no more than 10min in an oven at 136°C. In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 130°C.
[0249] Example I-9c
[0250] Refer to Example I-1, except that the repeating unit C is -CH2-CH2-CH2-, the number average molecular weight of the corresponding polymer microspheres is 323490Da, the melting point of the polymer microspheres is 122°C, and the air permeability of the diaphragm is 24480s / 100cc within no more than 10min in an oven at 136°C. In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 128°C.
[0251] Comparative Example I-1
[0252] The same procedure was followed as in Example I-1, except that no polymer microspheres were present in the composite layer.
[0253] Comparative Example I-2
[0254] Refer to Example I-1, except that the weight content of repeating unit B in the polymer microspheres is 2%, the weight content of repeating unit A is 66%, the weight content of repeating unit C is 32%, the corresponding number average molecular weight of the polymer microspheres is 462480Da, the melting point of the polymer microspheres is 145°C, the ratio of the weight proportion of repeating unit B in the polymer microspheres to the thermal shrinkage rate of the substrate layer in the TD direction is 0.87, and in an oven at 136°C, the air permeability of the diaphragm is 259s / 100cc within no more than 10min; in a temperature rise test of 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 152°C.
[0255] Comparative Example I-3
[0256] Refer to Example I-1, except that the weight content of repeating unit B in the polymer microspheres is 13%, the weight content of repeating unit A is 60%, the weight content of repeating unit C is 27%, the corresponding number average molecular weight of the polymer microspheres is 13960Da, the melting point of the polymer microspheres is 65°C, the ratio of the weight proportion of repeating unit B in the polymer microspheres to the thermal shrinkage rate of the substrate layer in the TD direction is 5.65, and in an oven at 136°C, the air permeability of the diaphragm is 28573s / 100cc within no more than 10min; in a temperature rise test of 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is 69°C.
[0257] Example II group is used to illustrate the separator in which the polymer microspheres are located in the polymer microsphere layer.
[0258] Example II-1
[0259] The method is carried out in accordance with Example I-1, except that the diaphragm is prepared according to the following method:
[0260] Substrate layer: polyethylene, the thickness of the substrate layer is 5 μm;
[0261] Ceramic layer: first inorganic particles: aluminum oxide, 85 parts by weight, first binder: polyvinylidene fluoride-hexafluoropropylene, 12 parts by weight, first auxiliary agent: polyethylene glycol, 3 parts by weight;
[0262] Polymer microsphere layer: polymer microsphere, 78 parts by weight; third binder: styrene-butadiene rubber, 12 parts by weight; third auxiliary agent: polyethylene glycol, 10 parts by weight; the thickness of the polymer microsphere layer is 3 μm.
[0263] Adhesive layer: polyvinylidene fluoride-hexafluoropropylene, the thickness of the adhesive layer is 1 μm.
[0264] The polymer microspheres, the third binder and the third auxiliary agent are added to 860 parts of DMAC, and the mixture is uniformly mixed to obtain a first mixed slurry. The first mixed slurry is coated on one side of the diaphragm substrate layer by micro-gravure printing to form a polymer microsphere layer. After drying, the first inorganic particles, the first binder and the first auxiliary agent are added to 860 parts of DMAC, and the mixture is uniformly mixed to obtain a second mixed slurry. The second mixed slurry is coated on the surface of the polymer microsphere layer by micro-gravure printing to form a ceramic layer. After drying, the surface of the ceramic layer and the other side of the substrate layer are respectively coated with a glue layer.
[0265] In the obtained diaphragm, the ceramic layer is located on one side of the substrate layer, the adhesive layer is located on the surface of the substrate layer and the ceramic layer, and the polymer microsphere layer is located between the substrate layer and the ceramic layer. In an oven at 136° C., the air permeability of the diaphragm is 48650 s / 100 cc within no more than 10 minutes.
[0266] Example II-2
[0267] Referring to Example II-1, the difference is that the position of the polymer microsphere layer, specifically, the ceramic layer is located on one side of the substrate layer, the adhesive layer is located on the surface of the substrate layer and the ceramic layer, and the polymer microsphere layer is located between the ceramic layer and the adhesive layer. In an oven at 136°C, the air permeability of the diaphragm is 11553s / 100cc within no more than 10 minutes.
[0268] Example II-3
[0269] Referring to Example II-1, the difference is that the position of the polymer microsphere layer, specifically the ceramic layer is located on one side of the substrate layer, the adhesive layer is located on the surface of the substrate layer and the ceramic layer, and the polymer microsphere layer is located between the substrate layer and the adhesive layer. In an oven at 136°C, the air permeability of the diaphragm is 53190s / 100cc within no more than 10 minutes.
[0270] Example II-4
[0271] Referring to Example II-1, the difference is that the position of the polymer microsphere layer, specifically, the ceramic layer is located on both sides of the substrate layer, the adhesive layer is located on the surface of the ceramic layer, and the polymer microsphere layer is located between the ceramic layer and the substrate layer. In an oven at 136°C, the air permeability of the diaphragm is 32430s / 100cc within no more than 10 minutes.
[0272] Example II-5
[0273] Referring to Example II-1, the difference is that the position of the polymer microsphere layer, specifically, the ceramic layer is located on both sides of the substrate layer, the adhesive layer is located on the surface of the ceramic layer, and the polymer microsphere layer is located between the ceramic layer and the adhesive layer. In an oven at 136°C, the air permeability of the diaphragm is 16512s / 100cc within no more than 10 minutes.
[0274] Test Case
[0275] The lithium ion batteries obtained in the embodiment and the comparative example were respectively subjected to the following tests:
[0276] 1. 136℃ furnace temperature test
[0277] The fully charged cells (100% SOC) obtained after charging and discharging the battery are placed in an oven and heated at 5°C / min. The temperature is raised to 136°C and kept warm for 1 hour. If fire or explosion occurs, it fails. If no fire or explosion occurs, it passes. A total of 3 batteries were tested and the results are expressed as "number of passes / 3".
[0278] 2. 45℃ Cycle Capacity Retention Test
[0279] At 45℃±2℃, the battery was charged to 4.53V at 0.7C constant current and constant voltage, cut off at 0.05C, and then discharged to 3.0V at 0.2C constant current. The initial discharge capacity was recorded as C0, and it was left at rest for 10min. The cycle format was: 3C constant current and constant voltage charging to 4.25V, cut off at 2C, switched to 2C constant current and constant voltage charging to 4.48V, cut off at 1.5C, switched to 1.5C constant current and constant voltage charging to 4.53V, cut off at 0.18C, rested for 5min, and discharged to 3.0V at 0.7C. After 300T cycles, the battery was charged to 4.53V at 0.7C constant current and constant voltage, cut off at 0.05C, and then discharged to 3.0V at 0.2C constant current, and the discharge capacity was recorded as C1. Capacity retention rate: C=C1 / C0*100%.
[0280] 3. Rate performance test
[0281] Stand at 25℃±2℃ for 10min, discharge at 0.2C to the lower limit voltage (3.1V), record the initial discharge capacity as Q0, stand for 10min, fully charge at 0.7C (100% SOC) in a constant temperature room (25℃±2℃), cut-off current 0.025C, stand for 10min, in a constant temperature room or incubator environment, discharge at 3C rate to the lower limit voltage (3.1V), stand for 10min, record the discharge capacity as Q1. Rate discharge capacity retention rate = Q1 / Q0*100%.
[0282] The obtained results are recorded in Table 1.
[0283] Table 1
[0284]
[0285]
[0286] *Indicates that the polymer microspheres of the lithium-ion battery of Comparative Example 1-3 have melted during the formation stage, and the cycle capacity retention rate and rate performance tests cannot be performed.
[0287] It can be seen from Table 1 that the battery made of the diaphragm of the embodiment has significantly improved furnace temperature passing conditions, improved battery capacity retention rate, and improved 3C discharge capacity retention rate, indicating that by adding polymer microspheres to the diaphragm and controlling the weight proportion of the group -CH2-CH(OCOCH3)- in the polymer microspheres, the safety performance, cycle stability and rate performance of the lithium-ion battery are improved.
[0288] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A diaphragm, characterized in that: The membrane comprises polymer microspheres, wherein the polymer microspheres comprise repeating units A, repeating units B and repeating units C, wherein the structural formula of repeating unit B is *-CH2-CH(OCOCH3)-*, and the repeating units A and C each independently comprise a substituted or unsubstituted C2-6 alkyl, One or more of the substituted substituents are selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3, * represents a connection end; the end group of the polymer microsphere is the repeating unit A and / or the repeating unit C, and the weight proportion of the repeating unit B in the polymer microsphere is 3%-10%.
2. The diaphragm according to claim 1, wherein At least one of the repeating unit A and the repeating unit C comprises a substituted or unsubstituted C2-6 alkyl group; And / or, the repeating unit A and the repeating unit C each independently comprise a substituted or unsubstituted C2-4 alkyl, One or more of, the substituted substituent is selected from chlorine, fluorine, cyclopropane, propoxy, butoxy, -COOH, -O-, -COOCH3; Preferably, the repeating unit A and the repeating unit C are each independently selected from ethyl, monochloroethyl, propyl, oxirane, difluoroethyl, One or more of .
3. The diaphragm according to claim 1, wherein The monomer forming the repeating unit B is vinyl acetate; And / or, the monomers forming the repeating unit A include substituted or unsubstituted C2-4 olefins, One or more of, the substituted substituent group is selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3; and / or, the monomers forming the repeating unit C include substituted or unsubstituted C2-4 olefins, One or more of, the substituted substituent group is selected from halogen, cyclopropane, ethoxy, propoxy, butoxy, -COOH, -O-, -COOCH3, -COOCH2CH3; And / or, the polymer microspheres are copolymers, and the polymer microspheres are formed by copolymerization of ethylene-vinyl acetate and one or more of the following compounds: polyethylene, polypropylene, polymethyl methacrylate, ethylene-propylene-diene copolymer, polyamide, polyester, polystyrene, polyacrylic acid-butadiene-styrene, polylactic acid, polyvinyl chloride, polyvinyl butyral.
4. The diaphragm according to any one of claims 1 to 3, wherein: The average particle size of the polymer microspheres is 0.01 μm-5 μm, preferably 0.3 μm-2 μm; And / or, the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the average particle size of the polymer microspheres is 3-50, preferably 6-25; And / or, the number average molecular weight of the polymer microspheres is 20000Da-500000Da; and / or, the weight proportion of repeating unit A in the polymer microspheres is 50%-77%; and / or, the weight proportion of the repeating unit C in the polymer microspheres is 20%-40%; And / or, the melting point of the polymer microspheres is 80°C-140°C.
5. The diaphragm according to claims 1 to 4, wherein: The separator comprises a substrate layer, and the ratio of the weight proportion of the repeating unit B in the polymer microspheres to the shrinkage rate of the substrate layer in the TD direction (105° C., 1 hour) is 0.5-30, preferably 2-10; Preferably, the thermal shrinkage rate of the substrate layer in the TD direction (105° C., 1 hour) is 0.5%-10%.
6. The diaphragm according to claim 5, wherein: The diaphragm further comprises a ceramic layer, a polymer microsphere layer and a glue layer, wherein the polymer microsphere layer comprises the polymer microspheres; the ceramic layer comprises first inorganic particles and a first binder; Preferably, the first inorganic particles include at least one of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, nickel oxide and zeolite; Preferably, the first binder includes polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth) acrylate, aramid resin, poly (meth) acrylic acid, styrene-butadiene rubber, polyvinyl alcohol, polyvinyl acetate, carboxymethyl cellulose, sodium carboxymethyl cellulose, carboxyethyl cellulose, polyacrylamide, phenolic resin, epoxy resin, water-based polyurethane, polyacrylic copolymer, lithium polystyrene sulfonate, water-based silicone resin, nitrile-polyvinyl chloride blend, styrene-acrylic latex, pure benzene latex, etc. and one or more of the blended and copolymerized polymers derived from the modified aforementioned polymers.
7. The diaphragm according to claim 6, wherein: The ceramic layer is located on one side of the substrate layer, the adhesive layer is located on the surface of the substrate layer and the ceramic layer, the polymer microsphere layer is located between the substrate layer and the ceramic layer, and / or the polymer microsphere layer is located between the substrate layer and the adhesive layer, and / or the polymer microsphere layer is located between the ceramic layer and the adhesive layer.
8. The diaphragm according to claim 6, wherein The ceramic layer is located on both sides of the substrate layer, the adhesive layer is located on the surface of the ceramic layer, the polymer microsphere layer is located between the ceramic layer and the substrate layer, and / or the polymer microsphere layer is located between the ceramic layer and the adhesive layer.
9. The diaphragm according to claim 5, wherein: The diaphragm further comprises a composite layer and a glue layer, wherein the composite layer is located on one side or both sides of the substrate layer, the glue layer is located on the surface of the substrate layer and / or the surface of the composite layer, and the components of the composite layer include second inorganic particles and polymer microspheres; Preferably, the second inorganic particles include at least one of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, nickel oxide and zeolite; Preferably, the zeolite comprises solid particles and / or particles containing a hierarchical pore structure; Preferably, the configuration of the zeolite includes one or more of MEI, BEA, RRD, STT, MWW, MFI, LTA, FAU, SOD, CHA and MOR.
10. The diaphragm according to claim 9, wherein Based on the total weight of the composite layer, the weight content of the polymer microspheres is 5%-40%, and the weight content of the second inorganic particles is 50%-90%; and / or, the ratio of the thickness of the composite layer to the average particle size of the polymer microspheres is 1-10; And / or, the thickness of the composite layer is 0.5 μm-10 μm; and / or, the average particle size of the second inorganic particles is 0.1 μm-10 μm; And / or, the ratio of the average particle size of the second inorganic particles to the average particle size of the polymer microspheres is 2-10, preferably 3.5-7.
11. The diaphragm according to any one of claims 5 to 10, wherein: The composition of the substrate layer includes one or more of polyethylene, polypropylene, polyimide, polyacrylonitrile and polyethersulfone; And / or, the thickness of the substrate layer is 3 μm-20 μm; And / or, the composition of the adhesive layer includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene modification and copolymers thereof, polyacrylonitrile, polymethyl methacrylate, polyacrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol and copolymer-modified polyvinyl alcohol thereof, polyvinyl acetate, polyacrylamide, phenolic resin, epoxy resin, water-based polyurethane, ethylene-vinyl acetate copolymer, polyacrylic acid copolymer, lithium polystyrene sulfonate, pure benzene latex, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyvinyl pyrrolidone, polyethylene oxide, cellulose acetate, butyl cellulose acetate, propyl cellulose acetate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose and cyanoethyl sucrose; And / or, the thickness of the adhesive layer is 0.1 μm-10 μm; And / or, in an oven at 136° C., the air permeability of the separator is higher than 10000 s / 100 cc within no more than 10 min.
12. A lithium ion battery, characterized in that: The lithium ion battery comprises the separator according to any one of claims 1 to 11.
13. The lithium ion battery according to claim 12, wherein: In a temperature rise test at 1°C / min, the temperature at which the internal resistance of the lithium-ion battery exceeds 1000Ω is lower than 136°C.
Citation Information
Patent Citations
Lithium ion battery composite diaphragm and preparation method and application thereof
CN104157811A
Mixed paint for composite membrane of lithium ion battery, composite membrane and preparation method thereof, and lithium ion battery
CN105304850A
Composite diaphragm for reducing thermal runaway risk of lithium battery, preparation method and lithium battery
CN111293262A
Lithium ion battery diaphragm, preparation method thereof and lithium ion battery
CN111697184A
Separator for lithium secondary battery, manufacturing method for same, and separator manufactured by the manufacturing method
CN115769430A
Cited By
Diaphragm, secondary battery, battery pack and electronic equipment
CN121394777A